SOCIAL SECURITY IN CRISIS CONDITIONS (Annual of the Faculty of Philosophy in Skopje, 2020)
The crisis, which began in 2019 and is ongoing in 2020, is based on a pandemicand has health and social consequences. Corona crisis has shaken the world on an unprecedentedscale. Comparisons with previous crises indicate dramatic and huge loss ofhuman life. The full mobilization of the states required them to take various measures.The measures are in the area of: health, social, economic, legal, political, hygienic, educational,fiscal, transport, security and so on. They are all complex and multidimensional,affecting many aspects of people's lives and social security. Border blockades, stoppingof air transport, rail and road traffic meant complete isolation of people. The drasticrestriction on the movement of people, as well as the consequences of these measureshave led to social uncertainty and phenomena that are not fully explained, and forwhich they should be seen in numerous scientific disciplines.Among the most visible consequences, in addition to health, are economic andsocial, which have been felt directly by all people. Probably for a long time to come, thesemeasures will produce limitations that explain the need to preserve people's healthand social security. The paper examines social security in times of crisis and the impactsthat arise from the institutional and systemic solutions offered.
Keywords: SOCIAL SECURITY; CRISIS; INSTITUTIONS; SOLUTIONS; MEASURES